Pemaknaan Lirik Lagu Feel Special ( Analisis Wacana Van Dijk ) - Sillvia Anggraini Joue Purnama Sari; Sapta Sari; Anis Endang SM (Jurnal Multidisiplin Dehasen (MUDE), 2024)
Song lyrics are verbal symbols created by humans. In expressing their experiences, songwriters play with words and language to create appeal and distinctiveness to their lyrics or verses (Awe, 2003:51). Twice's Feel Special depicts the importance of valuing oneself and finding happiness within oneself, without relying on the validation or recognition of others. It also describes feelings of doubt and uncertainty about one's worth. Therefore, the background explains that the song Feel Special has received many positive responses from fans and music critics. This Feel Special song remains relevant today because its message about self-worth is something that is relatable to many people. This song can be a source of strength and inspiration for those who are feeling a loss of confidence. This research uses a qualitative research method with van dijk's discourse analysis approach. This analysis focuses on the macro and micro structure of the song text, as well as the social context and social cognition. The results show that the lyrics of the song Feel Special contain the meaning of the importance of loving oneself and accepting one's shortcomings, as well as telling the story of a person who feels insecure and insecure, then he learns to become more confident. This message is conveyed through various discourse strategies, such as text, social cognition and social context. The meaning of this song can help its listeners to increase their self-confidence and self-acceptance.